1943
DOI: 10.1002/hlca.19430260715
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über Organextrakte. (3. Mitteilung). Zur Kenntnis der unverseifbaren Lipoide aus arteriosklerotischen Aorten

Abstract: 3. Mitteilungl)). Die hochgradig arteriosklerotische2) Aorta zeigt eine degenerativ entartete Innenhaut (Intima) mit reichlicher Lipoidinfiltration, oft auch mit Verkalkung und Geschwiirbildung. Die angehauften Lipoide bestehen vorwiegend aus Cholesterin und dessen Fettsaure-estern3). Ihre Menge ubersteigt den normalen Lipoidgehalt der Intima urn ein Vielfaches. Schon vor langcrer Zeit vertrat erstmals L. Aschoff4) die Ansicht, dass die fortschreitende arteriosklerotische Veranderung der grossen Arterien mit d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2
1

Year Published

1943
1943
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(13 citation statements)
references
References 15 publications
0
10
2
1
Order By: Relevance
“…These compounds have been found in the UM of organ extracts (cf. Hardegger et al 1943). Our observations do not, however, preclude its presence.…”
Section: Discussioncontrasting
confidence: 69%
“…These compounds have been found in the UM of organ extracts (cf. Hardegger et al 1943). Our observations do not, however, preclude its presence.…”
Section: Discussioncontrasting
confidence: 69%
“…Hardegger et al (15) analyzed a large mass of aortic tissue and found mostly cholesterol plus some oxidized derivatives of cholesterol. Their study was carried out before more sophisticated methods of analysis, such as GC, were available.…”
Section: Discussionmentioning
confidence: 99%
“…They have been found in intestinal fat, cavity fat and liver oil of rat, in the domestic hen (particularly in the egg yolk), 16,47 bone marrow and milk of cattle and man, 48 spleen of pigs, 49 erythrocytes, 50 and in atherosclerotic arteries of man, 51 to name a few tissues. Glyceryl ethers are present in neonatal calf but their concentrations decrease rapidly after birth.…”
Section: Biological Importance Of Glyceryl Ethers and The Monooxygmentioning
confidence: 99%